1993
DOI: 10.1063/1.109002
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature Si3N4 direct bonding

Abstract: Extremely strong bonds can be formed between smooth, clean layers of Si3N4 at temperatures ranging between 90 and 300 °C. These bonds have been formed between Si3N4 layers deposited on various substrates with deposition temperatures as low as 300 °C. The bond is initially formed at room temperature and subsequently annealed at temperatures ranging between 90 and 300 °C. Thus, the materials bonded in this manner are never exposed to temperatures higher than 300 °C. This low temperature bond greatly expands the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 12 publications
0
30
1
Order By: Relevance
“…This room temperature bonding method of LPCVD silicon nitride without any surface pre-smoothening processes (Bower et al 1993;Sanchez et al 1997) prior to bonding was not yet reported (as far as the authors knows). High surface energies are obtained when activating both wafers of a silicon nitride wafer bonding pair using either oxygen or argon plasma.…”
Section: Discussionmentioning
confidence: 91%
“…This room temperature bonding method of LPCVD silicon nitride without any surface pre-smoothening processes (Bower et al 1993;Sanchez et al 1997) prior to bonding was not yet reported (as far as the authors knows). High surface energies are obtained when activating both wafers of a silicon nitride wafer bonding pair using either oxygen or argon plasma.…”
Section: Discussionmentioning
confidence: 91%
“…It has also been found that the tensile strength of Pyrex-glass can be weaker than 10 MPa, as reported by Pegasus (www.pegasus-glass.com/pyrex.asp). Also, the failure strength of bulk Si is approximately 10 MPa (Bower et al 1993). Therefore, it is possible for debonding or breakup to occur inside the Pyrex glass or Si rather than at the site of bonding interface where the bond strength is greater than the failure strength of the glass or Si.…”
Section: Bonding Strengthmentioning
confidence: 97%
“…Further reduction in the bonding temperature has been obtained using ultra high vacuums with atomic H or Ar sputter cleaning procedures [18], [19]. An alternative route for joining III-V wafers is using hydrophilic Si-based layers [20], [21]. This approach avoids the requirement for ultra high vacuums, allows relatively low processing temperatures, enables the use of bonding procedures well-developed for Si-based materials, and provides less sensitivity to surface microroughness than hydrophobic bonding [5], [22].…”
Section: Introductionmentioning
confidence: 99%